Penyelesaian Perselisihan Tindak Pidana Kekerasan Fisik Dalam Rumah Tangga Melalui Peradilan Adat Gampong Berdasarkan Qanun Nomor 9 Tahun 2008 Tentang Pembinaan Kehidupanadat Dan Adat Istiadat (Stud iPenelitian di Kecamatan Syamtalira Aron Kabupaten Ace - Auliadi, Rizki (LPPM Universitas Almuslim, 2024)
Settlement of Disputes for Physical Violence in the Household can be resolved through the Gampong Customary Court based on Qanun Number 9 of 2008 concerning the Guidance of Customary Life and Customs. gampong customary courts, second, what is the mechanism for resolving domestic violence through gampong traditional institutions, third, what is the power of law against the settlement of criminal acts of domestic violence through gampong traditional courts. Criteria for Domestic Violence that can be resolved through the gampong customary court in Syamtalira Aron District, North Aceh Regency; second, to find out and analyze the mechanism for resolving domestic violence through traditional institutions in Syamtalira Aron District, North Aceh Regency; Third, to find out and analyze the power of law against the settlement of criminal acts of domestic violence through the gampong customary court in Syamtalira Aron District, North Aceh Regency. The type of empirical juridical research is field research that examines applicable legal provisions and what happens in reality in the community by examining problems that arise in the midst of society. One of the methods used is interviews. Research results: first; The criteria for disputes over physical violence in the household that can be resolved through the gampong customary court are the category of violence that does not cause serious violence that causes the victim to die. The mechanism for resolving disputes over physical violence in the household is to involve the head of the village, Tuhapeut, keuchik, imummeunasah, secretaries and scholars by first reporting the incident to their respective sub-districts until the report is forwarded to the level of tuhapeut by the head of the village and followed by joint deliberation between the keuchik, The general counsel, secretaries and scholars are then scheduled for a mediation event between the parties and in the end a peaceful or non-peaceful agreement will be formed. third; The force of law against disputes over physical violence in the household through the gampong customary court is clearly stated in Law Number 11 of 2006 concerning the Government of Aceh and Qanun Number 9 of 2008 concerning the Guidance of Customary Life and customs and each decision ends peacefully or not.